Programmable regulation of translation by harnessing the CRISPR-Cas13 system. Issue 18 (9th February 2023) - Montagud-Martínez, Roser; Márquez-Costa, Rosa; Rodrigo, Guillermo
Abstract : Development of a novel framework to regulate translation by repurposing the CRISPR-Cas13 immune system, exploiting a cell-free expression system for prototyping. Abstract : The ability to control protein expression at both the transcriptional and post-transcriptional levels is instrumental for the cell to integrate multiple molecular signals and then reach high operational sophistication. Although challenging, fully artificial regulations at different levels are required for boosting systems and synthetic biology. Here, we report the development of a novel framework to regulate translation by repurposing the CRISPR-Cas13 immune system, which uses an RNA-guided ribonuclease. By exploiting a cell-free expression system for prototyping gene regulatory structures, our results demonstrate that CRISPR-dCas13a ribonucleoproteins (d means catalytically dead) can be programmed to repress or activate translation initiation. The performance assessment of the engineered systems also revealed guide RNA design principles. Moreover, we show that the system can work in vivo . This development complements the ability to regulate transcription with other CRISPR-Cas systems and offers potential applications.